Флористичне різноманіття Кремінського лісового масиву - Shevchenko, D.Yu. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The species composition of flora in the Kremenian forest was set, which counts a 921 species of vascular plants, related to 392 genera and 108 families, the its is studied systematic, biomorphological, geographical, ecological and coenotical structures. The character of synantropisation flora of forest massive is exposed. The sosological estimation phytodiversity of region is carried out, selected and described his rarities component. As a result of researches it is offered to create new objects of the natural-protected fund in a region.